1996
DOI: 10.1002/jlac.199619961020
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior of Doubly Bridged Dewar Benzenes – Synthesis of Prismanes

Abstract: In this paper we report on the photochemistry of Dewar benzenes bridged at the 1,4‐ and 5,6‐positions and substituted at the 2,3‐positions. It was found that simple alkyl substitution leads to prismanes only to a minor extent. Introduction of phenyl groups into the 2‐ or 2,3‐positions gives the corresponding doubly bridged prismanes in yields up to 80% Pentamethylene‐bridged bis‐Dewar benzenes 19 rearrange upon irradiation to 22. Irradiation of the doubly bridged Dewar benzene derivatives with one ester group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Quite spectacularly, when neat samples of 15 are irradiated with 365 nm light, photoisomerization is followed by rapid crystal formation. Monitoring this process by 1 H NMR confirmed that the photoisomerization was indeed quantitative and gave no signs of byproducts such as prismane . All things considered, Dewar benzene 15 is an ideal example of a supramolecular protecting group for synthon 16 .…”
Section: Turning-on [6]annulenes:  Dewar Benzene Revisitedmentioning
confidence: 86%
See 1 more Smart Citation
“…Quite spectacularly, when neat samples of 15 are irradiated with 365 nm light, photoisomerization is followed by rapid crystal formation. Monitoring this process by 1 H NMR confirmed that the photoisomerization was indeed quantitative and gave no signs of byproducts such as prismane . All things considered, Dewar benzene 15 is an ideal example of a supramolecular protecting group for synthon 16 .…”
Section: Turning-on [6]annulenes:  Dewar Benzene Revisitedmentioning
confidence: 86%
“…Monitoring this process by 1 H NMR confirmed that the photoisomerization was indeed quantitative and gave no signs of byproducts such as prismane. 38 All things considered, Dewar benzene 15 is an ideal example of a supramolecular protecting group for synthon 16. Specifically, the protecting group eradicates the aryl moiety, thus inhibiting intermolecular arylaryl interactions that would otherwise promote crystallization.…”
Section: Turning-on [6]annulenes: Dewar Benzene Revisited 29mentioning
confidence: 99%
“…Among them, 1,2-disulfonylethenes are considerable organosulfone molecules , and emerge as versatile synthons in synthetic applications such as cycloaddition, radical elimination, and 1,2-rearrangement reaction . To date, several classic methods including oxidation, condensation, and addition reactions were well established for the production of the 1,2-disulfonylethenes. However, these approaches are always restricted to predecorated feedstocks, narrow substrate scopes, and/or multiple synthetic steps.…”
mentioning
confidence: 99%
“…An appropriate compound which was easily accessible was 8 (see Scheme 1). 6 We have therefore investigated the sulfinate elimination for 8 as well as for 11 and 14, both of which are readily available via a Diels-Alder reaction 7 and subsequent light induced [2 + 2] cycloaddition (Scheme 2). This assumption seemed reasonable because similar bridgehead olefins have been shown to be intermediates in other reactions, in which they were trapped by anthracene and furane derivatives.…”
mentioning
confidence: 99%